The subjection of power in the development of the modern subject: an interpretation of Judith Butler's theory - Blanco Ramos, Roberto (2023)
What relationships are established between the analytical categories of the modern subject and the subjectivation of power?. With respect to the first, the theoretical establishment developed has been oriented through diverse conceptualizations, where, together with the interpretation of the subject category, a new understanding based on oppositions arises and, in which the unquestionable, passes through that delimitation of the questionable. In this sense, this essay intends to continue delving into the theoretical dynamization of power and its link with psychic structures that affect the subjection process of the subject, based on the formulations described by Butler in his book: The Psychic Life of Power: Theories in Subjection. The article is articulated, in theoretical terms, from the combination of postulates of philosophy, psychoanalysis and gender studies. The text concludes and contributes to explain necessary proposals around the discussions established by social theory related to the production and regulation of the modern subject.